Spatial externalities between Brazilian municipios and their neighbours - Philippe de Vreyer; Gilles Spielvogel (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
Clustering of economic performance and growth in space has generated considerable research on the spillovers and linkages among geographical neighbours. In this paper, we study the growth process of a large sample of Brazilian municipalities for the period 1970-1996 and attempt to evaluate the spatial externalities at work among them. We estimate the convergence speed of per capita income among municipios and test whether spatial externalities are linked to local income growth. Conditionally on structural characteristics, we find evidence of convergence between municipios and of positive spatial dependence in growth. These two facts could help explain the persistent inequalities between municipios and the increasing clustering of poor localities in the Northeast region.
Keywords: O40; R11; R12; 330